Karakteristik Fisikokimia Mayonnaise Rendah Lemak Berbasis Isolat Protein Kedelai : Studi Formula Terbaik Berdasarkan Uji Hedonik - Elisa Tri Nursari; masrukan; Eman Darmawan; Dyah Titin Laswati (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2025)
Conventional mayonnaise is typically high in fat and cholesterol due to the use of oil and egg yolk as emulsifiers. This study aimed to develop a healthier alternative by formulating low-fat mayonnaise using soy protein isolate (SPI) as a plant-based emulsifier. The objective was to evaluate the physical and chemical properties of SPI-based mayonnaise selected through hedonic testing, and to compare it descriptively with a conventional sample (without SPI) and a commercial product. A Completely Randomized Design (CRD) was applied with five SPI concentrations: 0%, 1%, 2%, 3%, and 4%. Parameters observed included viscosity, texture, emulsion stability, color, pH, moisture, fat, and protein content. The 4% SPI formulation was identified as the most preferred based on sensory evaluation. Results showed that the 4% SPI sample had lower fat content (31.51%) and higher protein content (4.41%) than the reference samples. It also exhibited high viscosity (36,937.5 cP), good texture (0.094 N), excellent emulsion stability (96.80%), bright appearance (L=66.30; a=1.33; b=12.67), and a pH of 3.95. These findings suggest that SPI-based mayonnaise offers improved nutritional and physical qualities, making it a promising functional low-fat alternative favored by consumers.